RS codes and linear prediction techniques for land mobile satellite channels. - Trabelsi, Chokri. (University of Ottawa (Canada), 1990)
Reed-Solomon codes as nonbinary block codes with multiple burst-error-correcting capability are well suited for error control in fading channels. This thesis studies the effectiveness of Reed Solomon codes and provides a complete characterization of these codes for a class of land mobile satellite communication channels. Earlier studies on the performance of RS codes in mobile satellite channels did not consider shadowing. Furthermore, they considered only the slow fading case. In our simulation the effect of shadowing is taken into consideration and a fast fading assumption is used with system fading bandwidths of 1 to 10 percent of the transmission rate. This range of normalized fading bandwidths corresponds to vehicle speeds from 15 to 60 mph at bit rate of 2400 bps and 4800 bps for L-band carrier frequency. BER performance results show that RS codes can provide large improvement, however there is still 5 to 20 dB discrepancy between the performance in an AWGN channel and LMSAT channel. Therefore to obtain further improvement a novel receiver structure which employs fading prediction in conjunction with RS codes has been introduce and analyzed. With practical predictor lengths, simulated performance results show that the proposed technique greatly reduces the performance degradation caused by the fading channel.
Keywords: Engineering, Electronics and Electrical.